Ecological Impacts of Untreated Chicken Manure on Soil Health of a Few Poultry Farms in Osun State, Nigeria (Global Journal of Science Frontier Research, 2025)
The present work attempts to determine soil sustainability by recognizing the impact of untreated chicken manure on soil health status by applying the fertility content method in various site usages in a few poultry farms in the Osun State Nigeria Nearly all of the chicken manure generated in advanced countries is treated before application while in growing countries chicken manure treatment is insignificant Untreated chicken manure soil samples were collected from poultry arable land and bush fallow while forestland sites were served as control The chemical primary and secondary variables were determined utilizing standard procedures while minor nutrients contents were performed with Flame Atomic Absorption Spectrophotometer after wet acid digestion Quality monitoring measures included blank analysis spike recovery tests and standard calibrations Descriptive and inferential statistics were utilized for data analysis The fertility content ranges were 1 30 2 38 1 22 2 36 1 30-2 39 and 1 32 2 38 for poultry arable land bush fallow and forestland respectively Minor spatial variations in contents were found for all the chemical primary secondary and minor nutrient variables in all parts of the study sites Apart from organic carbon OC organic matter OM and Zn the degree of fertility content for all the rest variables was found to be far below the recommended ranges set by Food and Agriculture Organisation for cropland soils The condition subsequently demands suitable agricultural practices to sustain the fertility content in the sampling These methods might comprise such measures as spraying untreated liquid manure before spreading and applying onto arable land forestland pastures or food crops devising and adhering to a site-directed integrated nutrient management strategy intensive land management and cropping techniques and suitable farming methods
Keywords: land usage activities; untreated chicken manure; chicken sustainable management; soil health status; fertility content